Uniqlo Flash Sale: Marketing Strategy to Increase Purchase Intention - Ilmah, Khafidzotul; Pebrianggara, Alshaf; Yani, Muhammad (Universitas Sains dan Teknologi Komputer, 2024)
This research purpose to determine the influence of Search Engine Optimization, Online Advertising and Time Pressure on Purchase Intentiom at the Uniqlo Flash Sale. This research uses quantitative methods with a descriptive approach. The sampling technique used was purposive sampling with a total of 96 respondents. Data collection techniques by distributing questionnaires. The data analysis technique uses Partial Least Square (PLS) using the Smart-PLS Version 3.0 program. The results of this research show that there is an effect of Search Engine Optimization on Purchase Intention. Online Advertising also has an effect Purchase Intention. Meanwhile, Time Pressure has no effect on Purchase Intention.